(3GdeLdO GdKGfj ef JdNjU GdJHUQI aj GdJaSjQs - (3GdchGTj, CMeO Hf jhSa (B((3, J (B680(3g`(B)s
(3ChdgG (B:s
(3ShQI Gdcga ecjI EdG(B: (3hGUHQ faSc GdBjI Ch ef ChdgG Edi(B: (3LQRG hEf GdPjf BefhG hYedhG GdUGdMGJ GdBjJGf; aEf Pdc eOfjs
(3BNQgG (B:s
(3hSjYde GdPjf XdehG Cj efbdH jfbdHhf dCfgG GSJagGe JbOjQg(B: (3jfbdHhf GfbdGHG Cj efbdHs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs